2014
DOI: 10.1016/j.ejmech.2013.12.055
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of 2-oxonicotinonitriles and 2-oxonicotinonitrile based nucleoside analogues

Abstract: Drug resistance and emergence of new pathogens highlight the need for developing new therapeutic agents. We focused on 2-oxonicotinonitrile (2-ONN) as derivative of the natural product 2-pyridinone.(1) Herein, we describe the synthesis of 2-ONNs bearing two aryl groups, which we coupled with organohalides, including three glycosyl bromides, to prepare the nucleoside analogues. Coupling occurred mostly at the 2-ONN ring nitrogen to give the aimed targets, and in a few cases, it happened at the 2-oxo position gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Firstly, 2‐oxonicotinonitriles 1a‐f have been prepared via one‐pot condensation of aromatic aldehyde (namely, 4‐chlorobenzaldehyde, 4‐methoxybenzaldehyde, or 4‐nitrobenzaldehyde), ketone (2‐acetylthiophene, 2‐acetylpyridine, 2‐acetylphenanthrene, or 4‐hydroxyacetophenone), ethyl cyanoacetate, and an excess amount of ammonium acetate [28] (Scheme 1). The chemical structure of nucleobases 1a , 1b , and 1d has been described in the literature [28–30]. Currently, the structure of the new 2‐pyridones 1c , 1e , and 1f has been demonstrated from their spectral data.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, 2‐oxonicotinonitriles 1a‐f have been prepared via one‐pot condensation of aromatic aldehyde (namely, 4‐chlorobenzaldehyde, 4‐methoxybenzaldehyde, or 4‐nitrobenzaldehyde), ketone (2‐acetylthiophene, 2‐acetylpyridine, 2‐acetylphenanthrene, or 4‐hydroxyacetophenone), ethyl cyanoacetate, and an excess amount of ammonium acetate [28] (Scheme 1). The chemical structure of nucleobases 1a , 1b , and 1d has been described in the literature [28–30]. Currently, the structure of the new 2‐pyridones 1c , 1e , and 1f has been demonstrated from their spectral data.…”
Section: Resultsmentioning
confidence: 99%
“…The antifungal activities of the 2‐ONN derivatives were assessed against Candida albicans ATCC 10231 and Aspergillus niger ATCC 16404. Agar‐diffusion method was used to assess the antibacterial and antifungal activity of the tested compounds. The diameter of inhibition zone of the bacterial and fungal growth in mm was used to assess the preliminary antimicrobial activity of the tested compounds .…”
Section: Resultsmentioning
confidence: 99%
“…Agar‐diffusion method was used to assess the antibacterial and antifungal activity of the tested compounds. The diameter of inhibition zone of the bacterial and fungal growth in mm was used to assess the preliminary antimicrobial activity of the tested compounds . Significant and broad antibacterial activity was observed for all tested compounds (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nucleoside analogs are well-known potent antiviral agents ( De Clercq 2004 ). Abou-Elkhair et al (2014 ) reported a scaffold of 2-oxonicotinonitrile (2-ONN)-based acetylated nucleosides. The hybrids were designed on the basis of many published biologically active 2-ONN derivatives.…”
Section: Antiviral Activitymentioning
confidence: 99%